Challenges of nurses in preparing couples for childbirth (Research, Society and Development, 2020)
The study aims to meet the needs in preparing couples for childbirth. This is an exploratory study with a qualitative approach. For examine information was used Thematic Analysis. The quest was approved by the Ethics in Research Committee (CEP) of the Universidade Vale do Acaraú (UVA) with registration number 2.442.627. From the thematic analysis revealed three categories: paternal participation in pregnancy; Lack of professionals in the preparation of couples for childbirth; Methodologies / Resources used in the preparation of couples for childbirth. From the study was recognized to identify the challenges that nurses face to perform the preparation for childbirth. From the study, it was possible to identify the challenges that nurses face in preparing the couple for childbirth. The difficulty of involving the father in these approaches prevents nurses from working in PHC within this focus. In addition, the insecurity and distance of professionals with the theme has a strong negative contribution. Further studies are suggested addressing the theme and that aim to promote father involvement during labor and birth, aiming at qualifying the Brazilian parturition scene.